2022
DOI: 10.1002/pmrj.12854
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and perceived barriers in individuals with moderate‐to‐severe traumatic brain injury

Abstract: Introduction: Regular physical activity (PA), especially aerobic exercise, may benefit cognitive function in middle-aged and older adults, but promoting regular PA in individuals with traumatic brain injury (TBI) remains a challenge. Objective: To characterize PA and perceived barriers to PA in younger (<45 years) and middle age and older (≥45 years) individuals ≥1 year after moderate-to-severe TBI. Design: Multicenter survey study. Setting: Community. Participants: Persons who met the following criteria were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…A weakness of this study is low participation of four specific groups: people aged 18–35 years, people aged 65+ years, rural community dwellers and those from culturally diverse populations. However, Pham et al [ 71 ] suggest that key differences in age groups relating to perceptions of physical activity by people living with TBI are less pronounced after 45 years of age, and Rydén et al [ 72 ] found that DCE development interviews with patients across multiple countries generally produced consistent results, thus our process may not have suffered significantly from the lack of older and culturally diverse participants. Importantly, we plan to use survey implementation strategies that target people aged 18–35 years, people aged 65+ years, rural community dwellers and those from culturally diverse populations, which will ensure their views are represented in the final DCE data.…”
Section: Discussionmentioning
confidence: 88%
“…A weakness of this study is low participation of four specific groups: people aged 18–35 years, people aged 65+ years, rural community dwellers and those from culturally diverse populations. However, Pham et al [ 71 ] suggest that key differences in age groups relating to perceptions of physical activity by people living with TBI are less pronounced after 45 years of age, and Rydén et al [ 72 ] found that DCE development interviews with patients across multiple countries generally produced consistent results, thus our process may not have suffered significantly from the lack of older and culturally diverse participants. Importantly, we plan to use survey implementation strategies that target people aged 18–35 years, people aged 65+ years, rural community dwellers and those from culturally diverse populations, which will ensure their views are represented in the final DCE data.…”
Section: Discussionmentioning
confidence: 88%
“…
We read with great interest the report titled "Physical activity and perceived barriers in individuals with moderate-to-severe traumatic brain injury" by Pham et al on physical activity in individuals with traumatic brain injury (TBI). 1 We appreciate the authors' efforts to identify barriers to physical activity for individuals with TBI and how these barriers vary with age. The study concluded that the main barriers to physical activity for individuals with TBI are lack of motivation and time and fatigue.
…”
mentioning
confidence: 99%